Novel process for preparation of metal-polymer composite membranes for hydrogen separation. (5th July 2018) - Strugova, D.V.; Zadorozhnyy, M. Yu; Berdonosova, E.A.; Yablokova, M. Yu; Konik, P.A.; Zheleznyi, M.V.; Semenov, D.V.; Milovzorov, G.S.; Padaki, Mahesh; Kaloshkin, S.D.; Zadorozhnyy, V. Yu; Klyamkin, S.N.
Abstract: In the present work, a new preparation method for metal-polymer composite materials for hydrogen separation which consist of hydride-forming intermetallic compound LaNi5 and polyethylene was developed. According to this technique, the mechanical activation of the initial powder mixtures was employed to provide good interface between the phases. A series of composite membranes with various filler concentrations was synthesized and characterized by X-ray diffraction, scanning electron microscopy and differential scanning calorimetry. The gas transport properties of the obtained materials in relation to H2, O2, N2, CO2 and CH4 were tested. The results indicate that the addition of the hydride-forming intermetallic compound to the barrier polymer leads to significantly improved selectivity with respect to hydrogen. The proposed method can be considered as a promising approach to producing of high performance composite membranes for hydrogen separation. Graphical abstract: Highlights: Preparation of polyethylene/LaNi5 membranes via mechanical activation is developed. The technology provides activation and optimal interfacing of LaNi5 with polymer. The membranes containing 10% LaNi5 have maximum hydrogen selectivity. The addition of an intermetallic to a polymer is promising for hydrogen separation.